ANALISIS PENGARUH HARGA, PROMOSI DAN BRAND IMAGE TERHADAP CUSTOMER LOYALTY MINUMAN KOPI (STUDI KASUS PADA STARBUCKS COFFEE CITRALAND SURABAYA) - Putri, Rania Andarini; Yuliati, Nuriah; Laily, Dona Wahyuning (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2023)
Coffee consumption in Indonesia has increased in the last ten years. In urban areas consuming Coffee is a new lifestyle. Many Coffee shops have grown and developed that also provide products with similar services. This study analyzes the characteristics of consumers of Starbucks Coffee Citraland Surabaya Coffee drinks and analyzes the effect of price, promotion, and brand image on customer loyalty. This research was conducted in Starbucks Coffee Citraland. The sampling technique was a purposive sampling with a total of 90 consumers of Coffee drinks Starbucks Coffee Citraland. The sample criteria are consumers of Starbucks Coffee Citraland Surabaya Coffee drinks who make purchases at least 3 times. The analytical method uses SEM-PLS with the help of the SmartPLS version 4 application. This study showed that price, promotion, and brand image have a positive effect on customer loyalty for Coffee drinks Starbucks Coffee Citraland. Key words: brand image, coffee shop, customer loyalty, price, promotion